Funkcja moralizatorska sentencji Appiusza - Stankiewicz , Lucyna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
The article talks about the aphorisms of Appius (Appius Claudius Caecus, c. 360 BCE – 275 BCE), the first individualized figure in Latin literature. The author introduces the reader to the motifs of the aphorisms and at the same time proposes a translation of these verses.